Ukrainian entrepreneurship in Italy: Factors influencing the creation of ethnic ventures - Diego Matricano; Mario Sorrentino (Journal of Innovation and Entrepreneurship, 2014)
This paper investigates the factors affecting the creation of ethnic ventures in the enclave in order to determine whether immigrants can be considered opportunity or necessity entrepreneurs. The results are helpful to proceed with further reflections on how immigrants perceive the context they are in and on what should be done to foster their social and economic integration. In order to achieve the final aim, three categories of factors - pull, push and socio-demographic - affecting the creation of ethnic ventures in the enclave are considered and tested. Data were obtained from a questionnaire survey that was administered to Ukrainian entrepreneurs in the Municipality of Caserta in southern Italy. The results of a logistic regression model indicate that the factors affecting the creation of new Ukrainian ventures are housing area and age: if immigrants live outside the enclave and they are younger than forty years old, then they are more likely to create new ethnic ventures in the enclave. These results demonstrate that the Ukrainians in Caserta perceive the context they are in as unfavourable: they are necessity entrepreneurs who create new ventures just to overcome the discrimination and exclusion that they experience. Implications for policy makers and suggestions for future research are discussed in the last part of the paper.
Keywords: 650; Ethnic entrepreneurs; Opportunity and necessity entrepreneurs; Push and pull factors; New venture creation